2017
DOI: 10.1080/09687637.2017.1318113
|View full text |Cite
|
Sign up to set email alerts
|

Online training for substance misuse workers: A systematic review

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…Within this review, studies using more rigorous research methodology noted increases in knowledge both immediately following the web-based training, yet other studies using weaker methodological designs noted little or no change in knowledge following a web-based training (Herschell et al, 2010). A recent systematic review of web-based training methods for substance abuse counselors by Calder and colleagues (2017) was unable to draw definitive conclusions due to a small number of included studies; however, the authors suggested that web-based training may be effective under certain conditions. These two reviews highlight the need for further research on web-based training.…”
mentioning
confidence: 92%
“…Within this review, studies using more rigorous research methodology noted increases in knowledge both immediately following the web-based training, yet other studies using weaker methodological designs noted little or no change in knowledge following a web-based training (Herschell et al, 2010). A recent systematic review of web-based training methods for substance abuse counselors by Calder and colleagues (2017) was unable to draw definitive conclusions due to a small number of included studies; however, the authors suggested that web-based training may be effective under certain conditions. These two reviews highlight the need for further research on web-based training.…”
mentioning
confidence: 92%
“…We know very little about the extent to which these programmes and courses address the needs of the workforce or are taken up by the intended target group. Three papers in this special issue (Calder, Ainscough, Kimergård, Witton, & Dyer, 2017;Forberger, Riedel, & B€ uhringer, 2017;Pavlovsk a, Miovosk y, Babor, & Gabrhelik, 2017) offer a snapshot of educational approaches and highlight the diversity in training and education in the alcohol and drugs field.…”
Section: Editorialmentioning
confidence: 99%
“…The approach to the training was multidisciplinary in order to allow for various perspectives on research on alcohol and drug use with the hope of transferring this multi-disciplinarity into the day-today work and practice of the students and to provide examples of how to apply and synthesise findings from different disciplines. Calder et al (2017) examine the contemporary shift towards online training for substance misuse workers by providing a systematic review of online interventions. Their review reveals few studies of online learning for the alcohol and drug use workforce and those that have been reviewed, appear to be designed for an end user about whom there is very little knowledge and understanding.…”
Section: Editorialmentioning
confidence: 99%
“…Clinicians have also expressed satisfaction with DE methods, as they can be completed at the clinician's pace and are an alternative to more expensive training options (Powell, McMillen, Hawley, & Proctor, 2013). Several systematic reviews have been conducted on the effectiveness of DE methods for behavioral health clinicians (Calder, Ainscough, Kimergard, Witton, & Dyer, 2017;Jackson, Quetsch, Brabson, & Herschell, 2018). Together, these reviews concluded that DE methods may be effective in facilitating clinician knowledge and skill under certain circumstances, but the included studies were limited SUSTAINABILITY OF AN EVIDENCE-BASED TREATMENT 10 by numerous methodological concerns making it difficult to draw conclusions (Calder et al, 2017;Jackson et al, 2018).…”
Section: Trainingmentioning
confidence: 99%
“…Several systematic reviews have been conducted on the effectiveness of DE methods for behavioral health clinicians (Calder, Ainscough, Kimergard, Witton, & Dyer, 2017;Jackson, Quetsch, Brabson, & Herschell, 2018). Together, these reviews concluded that DE methods may be effective in facilitating clinician knowledge and skill under certain circumstances, but the included studies were limited SUSTAINABILITY OF AN EVIDENCE-BASED TREATMENT 10 by numerous methodological concerns making it difficult to draw conclusions (Calder et al, 2017;Jackson et al, 2018). While there has been an increased interest in the use of DE methods, additional research is needed to understand their effectiveness.…”
Section: Trainingmentioning
confidence: 99%